Retinopathy of Prematurity - Neonatologists' Experience (Journal of Bangladesh College of Physicians and Surgeons, 2014)
In Bangladesh advancement of neonatal care has increased the survival of preterm very low birth weight (VLBW) neonates and the incidence of Retinopathy of prematurity (ROP) is also increasing. The objective of this study was to identify the cases of ROP and their risk factors recorded during hospital stay. This was a prospective observational study at special care baby unit (SCABU) and Intensive care unit of Dhaka Shishu Hospital from July, 2006 to March, 2008 among premature (